Gastric metastasis as the first manifestation of an invasive lobular carcinoma of the breast - Maíra Teixeira Dória; Jonathan Yugo Maesaka; Sebastião Nunes Martins Filho; Thales Parenti Silveira; Gabriela Boufelli; Sheila Aparecida Coelho Siqueira; Edmund Chada Baracat; José Roberto Filassi (University of São Paulo, 2015)
Gastrointestinal metastases from breast cancer are rare and generally occur several years after the diagnosis of the primary lesion. The diagnosis of gastric metastasis as the initial presentation of breast cancer is even rarer and can potentially mimic gastric carcinoma. We report the case of a 66-year-old female patient submitted to a total gastrectomy because of the histological diagnosis of undifferentiated gastric carcinoma. During the surgical procedure, biopsies of the peritoneum and the liver were performed, which were consistent with metastatic breast invasive lobular carcinoma (ILC). The primary lesion of the breast was detected during the post-operative period, when a 4-cm-long lesion was detected on physical examination and mammography. The revision of the gastric biopsy confirmed the diagnosis of ILC. The authors call attention to the rarity of gastrointestinal metastases as the initial presentation of breast ILC.